SMARTPHONE APPLICATION: A REVIEW OF POTENTIAL USE FOR NURSING STUDENTS - Fitri Handayani (English Language Teaching and Research, 2017)
The advancement of Smartphone application has brought significant changes to people’s life.  The Smartphone is not only used as a communication tool but also lead people to do certain activities in multiple ways. Those ways include accessing information, looking for entertainment, making photos and videos, playing games, and using specific application features. For medical students, especially nursing students, using a medical application in the Smartphone can be one of the potential ways in learning English easily. It provides them an opportunity to get some types of learning activities meaningfully.  They can use of image and animation on the apps to learn basic medical English, create, share and reflect English medical materials through audio or text, and gain the information about healthcare domain. Thus, this paper gives a brief discussion of using Smartphone application in English language teaching by highlighting few samples of application and activities for nursing students. Key words: Smartphone application, nursing students, medical English